2021
DOI: 10.1177/18479804211002926
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study on microwave welding of thermoplastic using multiwalled carbon nanotubes as susceptor

Abstract: Despite manufacturers’ goal of molding single component products from plastics, the structures of some of the products are far too complex to be molded as a single piece. Therefore, assembly of subcomponents into the final products is important for the manufacturing of many plastic-based products. To date, welding is the most efficient joining method for plastics. In this study, multiwalled carbon nanotubes were proposed as the susceptor for the microwave welding of high-density polyethylene considering multiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The microwave absorption performance of carbonaceous materials such as carbon nanotube (CNT) and graphite were widely studied. It is reported that the existence of sp 2 π electrons in carbon structure are responsible for the excellent microwave absorption as well as their heating mechanism [15]. For this reason, carbonaceous materials are suitable to serve as microwave susceptor for microwave welding.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave absorption performance of carbonaceous materials such as carbon nanotube (CNT) and graphite were widely studied. It is reported that the existence of sp 2 π electrons in carbon structure are responsible for the excellent microwave absorption as well as their heating mechanism [15]. For this reason, carbonaceous materials are suitable to serve as microwave susceptor for microwave welding.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the welded joint attained higher bonding strength than PP itself and suggested that the formation of composite at the interface was the main reason of high joint strength. Foong et al also studied welding of PP using CNTs alone as susceptor, which is less timeconsuming than using PVA/CNTs composite coating susceptor [16]. However, acidic doping process was needed for conductive polymer before being used as a susceptor, while carbon materials such as CNTs and nano-graphite is carcinogenic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PPy reinforced by functionalized nano-carbon delivers an enhanced morphological features [8]. Continuously, PPy/f-MWCNT is considered as an excellent NCs compounds in which cost-effectiveness, high mechanical strength and chemical stability as well as relatively high electrical conductivity can be obtained; the latter is mainly attributed to the considerable surface area and good adhesion to substrate [9]. Simultaneously, f-MWCNT is a thought provoking reinforcement for polymer composite due to its high aspect ratio, porosity, corrosion resistance, low toxicity and electrical resistance, and large interfacial area [10].…”
Section: Introductionmentioning
confidence: 99%